PELATIHAN INOVASI PUDING KENTANG UNTUK PENINGKATAN NILAI TAMBAH DAN PEMBERDAYAAN EKONOMI MASYARAKAT DUSUN MARONGAN - Rofiqoh, Adzimatur; Latip, Abdul; Khusniyah, Minanda Hidayatul; Pamikatsih, Mutia (khidmatan, 2025)
This community service program was implemented in Dusun Marongan, Sukomakmur Village, Magelang Regency, focusing on community empowerment through potato pudding innovation training. This intervention was designed to address the problem of low economic value derived from the abundant potato harvest, as the produce was primarily sold as raw material. The methodology employed was Participatory Action Research (PAR), actively involving the local women of Dusun Marongan through surveys, socialization, and intensive hands-on training accompaniment. The results demonstrate a significant increase in the participants' technical skills to process potatoes into high value-added food products. The program successfully created value-added on the local commodity and generated new business opportunities that support the diversification of income sources. Therefore, this innovation training is proven effective in empowering the community's economy and supporting village self-reliance through the optimal utilization of local agricultural potential.